Why Chinese Mobile Phones Sells Their Products in Indonesia - R. A. Aryanti W. Puspokusumo (Binus Business Review, 2012)
This paper mainly discusses about strategy of China mobile phone manufacturer. Based on the interview with the manufacturer’s representative, we tried to comprehend the strategy behind the China mobile phone raid in Indonesia. As people know that mobile phone industry keeps on growing day by day, especially by the invention of the Android operating system, an open source OS with integrated capability. By having a free licensed OS, mobile phone manufacturer can focus mainly on their hardware development. Mobile phone industry is getting crowded by the appearance of new players from China. As the result of the interview shown, in short, the manufacturers are growing because of their innovations and ideas to create a new product with competitive price, usage of right media for promotion, and persistence in penetrating the Indonesian market. It is also through this paper that we hoped to invite young entrepreneur to join the manufacturing industry, as it is a fast growing industry that will surely be developed by the fresh ideas of the young generation of Indonesia.